Ultrathin sheets of metal or metal sulfide from molecularly thin sheets of metal thiolates in solution - Busupalli, Balanagulu; Kummara, Sreenivas; Kumaraswamy, Guruswamy; Bhagavatula L. V. Prasad (Chemistry of Materials, 2014)
Materials that exist as single molecule thick twodimensional sheets are in great demand because they hold promise as precursors for synthesis of layered functional materials. We demonstrate that metal thiolates, that exist as lamellar assemblies in the neat state, can be disassembled into individual molecular sheets simply by dilution in apolar organic solvents and that these can form ultrathin metallic layers on substrates upon heat treatment. We establish the pathway to the disassembly of metal thiolates in solution using a combination of techniques, including X-ray diffraction, light scattering, FTIR, and TEM. Our results indicate that the lamellar structure of Pd-thiolates is preserved in toluene up to a concentration of 300% w/v and the average intersheet distance is unchanged. Interestingly, the dynamics of the Pd-thiolate sheets remain correlated even on diluting them up to 30% w/v, though the disorder within the lamellar stacks increases with a decrease in their coherence length. Finally, at dilutions less than about 5% w/v, individual sheets of these structures can be accessed that are isolated and directly observed using TEM. Heat treatment of the ultrathin films of metal thiolates deposited on appropriate substrates resulted in the formation of metal or metal sulfides with retention of sheetlike morphologies.